Optimal operation scheduling of Nam Ngum-1 and Nam Leuk hydropower plants - Deevanhxay P. (2015)
This work is concerned with hydropower scheduling procedure, applied from economic dispatch problems, to determine the optimal operation scheduling of Nam Ngum-1 and Nam Leuk hydropower plants. The hydropower plant was formulated as a nonlinear optimization problem and solved by using the modified lambda iteration method. This objective function was considered to minimize water discharge rate by using the quadratic function cost of generator to take power balance. The simulation results have shown that water can be saved about 7.15% of actual water discharge of January of 2010. © 2012 IEEE.